Residential care and cultural identity : exploring the challenges experienced by adolescent boys living at Epworth Child and Youth Care Centre in Lambton, Germiston - Malatji, Hlologelo (My University, 2017)
Teenage pregnancy is a growing social problem in South Africa and has, over the years extended to schools, particularly public schools. This is evident by the fact that each and every year, a significant number of teenage girls drop out of school because of pregnancy related issues. This is further exacerbated by a massive shift occurring in affected learners' lives following childbirth. They are expected to continue with school while at the same time cope with parental responsibilities related to teenage motherhood. It should be noted some learners do re-engage with education following the birth of their children. However, very little is known about the challenges they are confronted with after making the decision to go back to school. Thus the aim of this study was to explore the challenges experienced by teenage mothers when they re-engage with secondary school education after giving birth. The study adopted a qualitative research approach. A snowball sampling technique was used to sample 15 teenage mothers, while a purposive sampling technique was used to select 2 key informants. A semi-structured interview schedule was utilised as the research tool, with indepth one-on-one interviews used as a method of data collection. The collected data was analysed using thematic content analysis. Findings derived from the study revealed the desire to have a better future and the fear of being the black sheep of the family motivated teenage mothers to re-engage with school following child birth. However, it was also found reengaging with school after giving birth was a challenge for teenage mothers. This was alluded to by the lack of parental involvement in teenage mothers' day to day activities, hostile educators and the pressure of having to catch-up with missed work. In conclusion, even though some teenage mothers re-engage with education after giving birth, it is not an easy road to travel as it does severely affect teenage girls' access to education. Therefore, support is required from various stakeholders to support teenage mothers who decide to go back to school following the birth of their children. Recommendations related to policy improvement and future research are provided.
Keywords: Children -- Institutional care -- South Africa.; Teenage boys -- South Africa.